Active head rotation in benign positional paroxysmal vertigo - Ganança, Fernando Freitas [UNIFESP] (2009)
Benign Positional Paroxysmal Vertigo (BPPV) is one of the most common vestibular diseases and the active head rotation test one of the most modern methods of vestibular function assessment. AIM: this study aims to verify if the active head rotation test may reveal signs of horizontal and/or vertical vestibulo-ocular reflex dysfunction in vertigo patients suspected for BPPV. STUDY DESIGN: retrospective series study. MATERIALS AND METHOD: Neurotological evaluation including computerized electronystagmography and active head rotation on the horizontal and vertical axes were conducted in 100 patients suspected for BPPV patients. Results: Isolated or associated abnormalities of the horizontal and/or vertical vestibulo-ocular reflex gain, phase and symmetry were indicative of vestibular involvement and found in 77.0% of the BPPV patients. CONCLUSION: the active head rotation test revealed horizontal and/or vertical vestibulo-ocular reflex dysfunctions in a relevant number of BPPV patients.